Experiences of people with intellectual disability and dementia: A systematic review. Issue 2 (23rd December 2022) - Jacobs, Paula; Watchman, Karen; Wilkinson, Heather; Hoyle, Louise; McGenily, Laura
Abstract: Background: Dementia disproportionately affects people with intellectual disability. Most qualitative studies explore their experiences by utilising proxy‐reports. A smaller number of studies illustrate the possibility of exploring perspectives directly from people with intellectual disability and dementia. Method: This systematic review synthesised findings from existing studies ( n = 8) that involve people with intellectual disability and dementia as participants to understand their experiences of dementia. Searches were conducted using CINAHL, PsychInfo and Social Services Abstracts. Results: Findings include descriptions of changes in individual functioning, a narrowing of social worlds and of how people made sense of the changes despite often having no knowledge of their dementia diagnosis. Additionally, discussion focuses on how people's experiences are shaped by their environments. Conclusion: The review recognises the complexities of speaking to people with intellectual disability about dementia, challenges views that people with intellectual and dementia cannot be involved in research and makes recommendations to support inclusion in future studies.